Nitrogen fertilization influences flowering performance of lowland cut chrysanthemums. - Hassan, Siti Aishah; A. M, Asiah; Ramlan, Mohd Fauzi; A. K., Salbiah (2001)
Six levels of nitrogen were used to determine the appropriate level of N for cut chrysanthemum grown in soil less culture under lowland conditions. Chrysanthemums require high level of N for early maturity and vase life. However, higher N did not increase flower size. The carbohydrate content increased with high N levels. Based on our data, chrysanthemum grown in soil less culture under lowland conditions require between 200 to 300 mgL1 of N for shorter production period and possibly improved vase life as well.